Ablation behavior of Cf/ZrC-SiC and Cf/SiC composites produced by precursor infiltration and pyrolysis combined with gaseous silicon infiltration. (December 2022) - Yan, Chunlei; Li, Qiang; Shi, Yiang; Luo, Peng; Chen, Liyun; Long, Liang; Liu, Rongjun
Abstract: The ablation behavior of Cf /ZrC-SiC and Cf /SiC composites by a novel combined process was studied. The FLUENT calculation indicates high thermophysical gradients of oxyacetylene torch, which determines ablation behavior of the composites. The integrated effects of oxidation, evaporation and mechanical factor result in discontinuous SiO2 scale, thus causing severe ablation of Cf /SiC composites. As for Cf /ZrC-SiC composites, the joint action of ZrO2 and SiO2 bilayer structure provides good ablation and oxidation resistance. Nevertheless, a little erosion of Cf /ZrC-SiC composites occurs by the integrated effects of chemical and physical erosion, and the mechanical factor plays a more important role. Highlights: The growth of ZrC content accounts for better ablation performance of Cf /ZrC-SiC composites by a novel PIP-GSI process. FLUENT calculation indicates high thermophysical gradients of oxyacetylene torch, which determines the ablation behavior. The integrated effects result in discontinuous SiO2 scale, thus causing severe ablation of Cf /SiC composites. Joint action of ZrO2 and SiO2 bilayer structure provides good ablation and oxidation resistance for Cf /ZrC-SiC composites.